1968
DOI: 10.1515/cclm.1968.6.3.132
|View full text |Cite
|
Sign up to set email alerts
|

The Isoenzymes of Lactate Dehydrogenase in the Nephton of the Healthy Human Kidney

Abstract: Die Isoenzymmuster der LDH wurden in mikrosezierten anatomischen und f unktionellen Einheiten des Nephrons der gesunden Mehschenniere bestimmt. In denGlomeruli war die Aktivität von LDH-2 undLDH-5 niedrig, während die anderen Fraktionen wesentlich stärker und ungefähr gleich aktiv waren. In den gewundenen Harnkanälchen und in den Medullarstrahlen warLDH-1 die aktivste Fraktion, gefolgt von LDH-2, während nur wenig LDH-3 und fast keine Aktivität von LDH-4 und LDH-5 gefunden wurde. Zur Papille hin nahm die Aktiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1970
1970
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Serum LDH was higher when the diagnosis was ischemic ATN, and above 1173 U/L, the specificity for the diagnosis of ischemic ATN even reached 100%. However, because of the low [9][10][11][12][13] The plasma membrane is impermeable to LDH unless it loses its integrity when necrosis happens. A recent study found an association between plasma LDH levels and the extent of in vivo tubular injury in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum LDH was higher when the diagnosis was ischemic ATN, and above 1173 U/L, the specificity for the diagnosis of ischemic ATN even reached 100%. However, because of the low [9][10][11][12][13] The plasma membrane is impermeable to LDH unless it loses its integrity when necrosis happens. A recent study found an association between plasma LDH levels and the extent of in vivo tubular injury in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The kidneys contain the highest concentration of LDH of all human organs found mostly in tubular cells. 9 Because of its abundance, elevated levels of serum LDH may serve as a marker of tubular injury. However, only few very old studies have assessed the potential use of serum LDH as a marker of tubular damage in the clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…The separation of cortex and papilla is very coarse and does not take into account structural differences within these zones. With microdissec tion of the anatomical and functional units of the healthy human kidney and subsequent determination (cellulose acetate gel strips) of the LDH isoenzyme patterns Mattenheimer [13,89] showed low activity of LDH 2 and LDH 5 in glomeruli, while the other fractions were more and about equally active; in convoluted tubules and me dullary rays LDH 1 was the most active fraction followed by LDH 2 with little activity of LDH 3 and almost none of LDH 4 and LDH 5. Towards the papilla the activity of LDH 1 and LDH 2 decreased, while LDH 3 and LDH 4 became increasingly prominent.…”
Section: Enzymes Classifiedmentioning
confidence: 99%